The Impact of University of Zululand Structural and Cultural Contexts on Postgraduate Supervision Practice (2011–2016). Issue 2 (3rd April 2018) - Isike, Christopher
ABSTRACT: There is a constant interplay between the "people" ( agency ) and the "parts" ( structure and culture ), not only in teaching and learning, but also in postgraduate supervision practices globally. However, in South Africa, the tendency to use structure (higher education architecture, institutional history, institutional rules, policies and procedures) to address all challenges related to postgraduate (especially doctoral) studies has resulted in university managers ignoring the role that institutional research culture (social norms, expectations and practice) plays, not only in perpetuating some of these challenges, but also in understanding and resolving them. At the University of Zululand (UniZulu), these factors combine to affect not only the postgraduate supervision practices of supervisors, but also the quality of doctoral throughput (doctorateness) with overall implications for society in general. This article is a critical self-reflection on the author's postgraduate supervision practice at UniZulu between 2011 and 2016 with a view to highlight how structure and culture combine to impact on his supervision work at the institution. The discussion shows how these factors impact on the quality of doctoral output with implications for the author's practice and society in general. To deal with the challenges arising from the discussion, the article recommends: establishing a dedicated postgraduate studies unit headed by a director or dean as supervisors and supervisees need a support system that functions optimally; improving staff qualifications and training of supervisors to keep up with best practice in postgraduate supervision; and the Department of Higher Education and Training factoring differentiation realities into its funding modules for universities.